Development of Pyrimidinon Derivative Compounds from Methoxy Bis-Chalcone Analogs as Potential Anticancer Candidates - Nia Tussholiha (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to evaluate its bioactivity as a candidate anticancer compound through inhibition testing of dihydrofolate reductase enzyme activity. Methodology: Organic synthesis methods through condensation and cyclization, reflux, recrystallization, preparative thin layer chromatography, Fisher John Melting Point Apparatus, ultraviolet visible spectrometer, nuclear magnetic resonance spectrometer, mass spectrometer, infrared spectrometer, centrifugation, in vitro dihydrofolate reductase enzyme inhibition test, probit analysis, methotrexate as a positive control, and evaluation of anticancer bioactivity. Main Findings: The pyrimidinone derivative compound was successfully synthesized and confirmed through physical and spectroscopic characterization. The test results showed significant inhibitory activity against the dihydrofolate reductase enzyme. The synthesized compound had a fifty percent inhibitory concentration of 25.086 micrograms per milliliter, lower than the positive control, indicating better anticancer potential and high inhibitory effectiveness. Novelty/Originality of this study: The novelty of this research lies in the synthesis of pyrimidinone derivatives based on bis-chalcone analogs containing methoxy groups, which have not been widely studied as anticancer candidates. This study provides new insights into the relationship between structure and biological activity, while also expanding the development of heterocyclic compounds as dihydrofolate reductase inhibitors for anticancer therapy.